Brazilian High School in dictatorship (1964-1985): critical analysis of its functions (Research, Society and Development, 2020)
Brazilian bourgeois-military dictatorship (1964-1985) reconfigured educational policy and left a legacy that persists and implies constant studies. This research analyses especially the High School guidelines in dictatorial period, so-called Second-degree teaching, identifying its functions. Based on qualitative and bibliographic analysis as well as with historical materialism as theoretical contribution, it articulates structural and ideological elements required by the capital, such as the educative reforms of that period. Redefinition of the Second-degree teaching was guided by the Human Capital Theory and the National Security Doctrine within the Capital’s Taylorist-Fordist logic is among the findings. With the Law number 5.692/1971, instrumental qualification for work was prioritized in this teaching, as well as a conservative ideology was internalized to ensure political conditions to reproduce the imperialist order in Brazil.